Metamorphosis from virtual community to 'For Benefit' enterprise: chronicle of PULA and PULA Exclusives Pvt. Ltd. Issue 2 (27th December 2021) - Dam, Leena B.; Pillai, Deepa
Abstract : Theoretical basis: The instructor should discuss the various forms of organization. Particular reference needs to be drawn on "For Benefit" firms. How such firms enable societal development should be stressed upon. Other theories considered are "need achievement theory", "self-determination theory" and "social cognitive theory." Research methodology: The primary data for the case was from a series of in-depth interviews and interactions with Sonia and her core team members of Bazaar and Approval Teams. Frequent deliberation with the founder and core team led to interesting dialogues on the aspiration to uphold Pune Ladies Association (PULA) Exclusives Pvt. Ltd. as a "For Benefit firm" and developing indigenous women entrepreneurs which was a stimuli for writing the case. Online surveys of the PULA verified sellers were conducted to identify their rationale of starting the venture and also their experiences on the PULA platform. Case overview/synopsis: March 2019, the core committee of PULA Exclusives Pvt. Ltd. (the firm) engineered a dialogue. They wanted to expand a new horizon with its mission of "For Benefit". The firm is an offshoot of PULA, a virtual women's community in Facebook. Complexity academic level: The case may be used for postgraduate students pursuing entrepreneurship and management courses. The case can be used for teaching executive level programs of business strategy and digital media. The case applies to the use of digital media in businesses, social entrepreneurship and innovation strategies.